Anker Jørgensen: Bølgegang. Fra mine dagbøger 1972-1975 (462 s., 1989), I smult vande. Fra mine dagbøger 1975-1977 (499 s., 1989), Brændingen. Fra mine dagbøger 1978-1982 (579 s., 1990). Fremad. - Dybdahl, Vagn (Historie/Jyske Samlinger, 1991)
-